Kesediaan Membayar Terhadap Layanan Battery Tram Koridor Kuta, Bali - Fransiscus Rian Pratikto (Institut Transportasi dan Logistik Trisakti, 2023)
The Government of Bali is planning to develop a battery tram mass rapid transport in the Kuta area as an effort to resolve severe congestion problem in that area. This research aims to measure consumers’ willingness to pay for the battery tram services in the Kuta corridor. The willingness to pay is measured using a survey based stated preference technique, the Contingent Valuation Method, with the Dichotomous Choice with Follow Up elicitation technique. An electronic survey targeting local residences and tourists that are considered potential users managed to collect 635 data. The survival analysis statistical technique is used to measure the willingness to pay assuming a lognormal distribution. The Survival Package from R software is used to produce the price-response function. The result shows that 50% of local residents are willing to pay up to Rp978/km, while 50% of tourists are willing to pay up to Rp4,402/km for the battery tram services. In general, the price-response curve shows that tourists are willing to pay Rp3,000-Rp5,000/km higher than local residents, most of the respondents that are reluctant to use the battery tram consider the offered prices in the CVM questionnaire too high or tend to avoid using public transport for health reason following the Covid-19 pandemic.